Pelatihan Pembuatan Video Profile Sebagai Strategi Dalam Meningkatkan Pendaftaran Siswa di SD Negeri 2 Ngesrep Boyolali - Putra, Tommy Dwi; Kusumastuti, Rajnaparamitha; Abdullah, Robi Wariyanto; Oktafiani, Dewi; Turmudi, Hadis (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service conducted aims to increase new student registration at SD Negeri 2 Ngesrep Boyolali through training in making school profile videos. In the digital era, online marketing and promotion are key to attracting the attention of parents and prospective students. An attractive profile video can provide a positive picture of the environment and advantages of the school, thus encouraging interest in registration. This activity involves training in profile video making techniques, starting from introducing tools, taking pictures, to promotional strategies through social media and paid advertising. The results of this training are expected to improve the skills of teachers and staff in making effective videos. Thus, schools can utilize digital platforms such as YouTube and Instagram to expand the reach of promotions. Obstacles faced during the implementation include scheduling between school and campus activities. Nevertheless, this training has been successfully implemented, and the resulting profile video is expected to increase the visibility and reputation of SD Negeri 2 Ngesrep Boyolali. Through this service, it is hoped that the number of new student registrations will increase significantly, so that the school can be better known by the wider community. This study shows that the use of video as a promotional medium is an effective strategy in supporting new student registration in today's digital era.